The Uses of Artificial Intelligence and Academic Ethics Awareness on The Learning Performance: Digital Literacy Abilities as Mediation Variable - Aulia Putri Setiowati; Fitriana Rahmawati (Journal of Office Administration : Education and Practice, 2025)
This study is based on the phenomenon of increasingly sophisticated technological developments in the era of education 4.0 which is able to help users in facilitating a better learning process. The sophisticated technology referred to in this study is the integration of the use of Artificial Intelligence (AI) in the learning process. This quantitative research with the Path Analysis model aims to determine the effect of the Use of AI and Academic Ethics Awareness on Learning Performance through Digital Literacy Skills. The Planned Behavioral Theory in this study explains how someone can achieve the desired behavior based on three important factors. The respondents in this study were students of the 2021-2024 Office Administration Education Study Program, Surabaya State University. Data testing using PLS-SEM. The results of the study showed that there was an influence between the Use of AI on Digital Literacy Skills, Academic Ethics Awareness had an effect on Digital Literacy Skills, Digital Literacy Skills had an effect on Learning Performance, the Use of AI had an effect on Learning Performance, Academic Ethics Awareness had an effect on Learning Performance, the Use of AI had an effect on Learning Performance through Digital Literacy Skills and Academic Ethics Awareness had an effect.